L’oeil-araignée. Descriptive systems like optical boxes in Diderot’s "Salons". A reading starting from Hamon’s theses - Crivella, Giuseppe (e-Scripta Romanica, 2020)
The text aims to analyse how the descriptive systems work in the Salons of Diderot. Retrieving the dense network of operational definitions developed by Philippe Hamon in the well-known text Du descriptif, our study develops a series of analyses aimed at highlighting the distance of Diderot’s descriptive practice with respect to the theoretical statements of the rhetorical treatise before him or coeval, focusing above all on an absolutely original use of the pantonyme within the Salons.